A collection of cannabinoid-related negative findings from autaptic hippocampal neurons - Straiker, Alex; Dvorakova, Michaela; Bosquez-Berger, Taryn; Blahos, Jaroslav; Mackie, Ken (Scientific reports, 2023)
Autaptic hippocampal neurons are an architecturally simple model of neurotransmission that express several forms of cannabinoid signaling. Over the past twenty years this model has proven valuable for studies ranging from enzymatic control of endocannabinoid production and breakdown, to CB1 receptor structure/function, to CB2 signaling, understanding 'spice' (synthetic cannabinoid) pharmacology, and more. However, while studying cannabinoid signaling in these neurons, we have occasionally encountered what one might call 'interesting negatives', valid and informative findings in the context of our experimental design that, given the nature of scientific publishing, may not otherwise find their way into the scientific literature. In autaptic hippocampal neurons we have found that: (1) The fatty acid binding protein (FABP) blocker SBFI-26 does not alter CB1-mediated neuroplasticity. (2) 1-AG signals poorly relative to 2-AG in autaptic neurons. (3) Indomethacin is not a CB1 PAM in autaptic neurons. (4) The CB1-associated protein SGIP1a is not necessary for CB1 desensitization. We are presenting these negative or perplexing findings in the hope that they will prove beneficial to other laboratories and elicit fruitful discussions regarding their relevance and significance.
Keywords: nervový přenos; Synaptic Transmission; Hippocampus; Neurons; hipokampus; Cannabinoids; Endocannabinoids; neurony; kanabinoidy; endokanabinoidy